2009
DOI: 10.1002/chem.200901127
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphine‐Functionalized Cyclic Decapeptides Based on the Natural Product Gramicidin S: A Potential Scaffold for Transition‐Metal Coordination

Abstract: The natural product Gramicidin S is a promising scaffold for novel oligopeptide-based bisphosphine ligands, combining the advantageous rigid chiral backbone with the close proximity of phosphine substituents. The required unnatural, phosphine-containing, amino acid building blocks were synthesized by means of a novel protocol that involves the enantioselective alkylation of a chiral nickel Schiff base template. Three Ni complexes were prepared with different alkyl chains between the phosphine group and the alp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 81 publications
0
13
0
Order By: Relevance
“…Lammertsma et al. reported biphosphane analogues of Gramicidin S, a cyclic decapeptide containing a rigid structure enforced by two β‐turns 33. These peptides were synthesised on solid support by replacement of two ornithines with phosphane‐containing amino acids.…”
Section: Peptide‐based Ligands For Transition‐metal Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…Lammertsma et al. reported biphosphane analogues of Gramicidin S, a cyclic decapeptide containing a rigid structure enforced by two β‐turns 33. These peptides were synthesised on solid support by replacement of two ornithines with phosphane‐containing amino acids.…”
Section: Peptide‐based Ligands For Transition‐metal Catalysismentioning
confidence: 99%
“… Bisphosphane‐modified Gramicidin S: a) crystal structures of two of the synthesised structures by Lammertsma et al. containing sulfur‐protected phosphanes 33. b) Structures applied in palladium‐catalysed asymmetric allylic substitution and rhodium‐catalysed asymmetric hydrogenation 34…”
Section: Peptide‐based Ligands For Transition‐metal Catalysismentioning
confidence: 99%
“…Bisphosphane-modified Gramicidin S: a) crystal structures of two of the synthesised structures by Lammertsma et al containing sulfurprotected phosphanes. [33] b) Structures applied in palladium-catalysed asymmetric allylic substitution and rhodium-catalysed asymmetric hydrogenation. [34] www.chemeurj.org leaching was significantly reduced by positioning the phosphane ligands at different sites in the dendrimer interior, which allowed several recycling cycles in hydroformylation.…”
Section: Other Oligopeptide Design Strategiesmentioning
confidence: 99%
“…Lammertsma et al reported biphosphane analogues of Gramicidin S, a cyclic decapeptide containing a rigid structure enforced by two b-turns. [33] These peptides were synthesised on solid support by replacement of two ornithines with phosphane-containing amino acids. X-ray crystal structures of two of these cyclic peptides containing sulfur-protected phosphanes show that the phosphane amino acids are in a favourable conformation for diphosphane complex formation (Scheme 5a).…”
Section: Oligopeptide-modified Phosphane Ligandsmentioning
confidence: 99%
“…This was found useful in asymmetric transition‐metal, and organo‐catalyzed reactions, bioinspired outer‐coordination‐sphere functionalized catalysis, mimicking redox‐enzyme functions, allowing electrochemical oxidation of hydrogen, use in fuel cells, oxidation of formic acid, and hydrogenation of carbon dioxide to formate via coupled proton and electron transfer . Also three structurally characterized bisphosphanyl‐functionalized gramicidin (S) derivatives for binding transition metals and bioconjugates with R 2 P‐coordinated radionuclides 186/188 Re and 99m Tc were reported, which are potential chemo‐ or radiotherapeutic agents . The PR 2 groups of the phosphanyl α‐amino acids (or peptides) are bound directly or via a suitable spacer, either at a carbon atom or via the (terminal) amino group.…”
Section: Introductionmentioning
confidence: 99%